An exploratory comparative effectiveness analysis of febrile neutropenia incidence among patients with cancer receiving granulocyte colony stimulating factors. Issue 28 (1st October 2022) - Pawloski, Pamala A.; Lockhart, Catherine; Vazquez-Benitez, Gabriela; DeFor, Terese A; Mendelsohn, Aaron; Marshall, James; Moyneur, Erick; McDermott, Cara L.
Abstract : 408 Background: We conducted an exploratory comparative effectiveness analysis comparing various G-CSF (pegfilgrastim/filgrastim) products to each other in incidence of febrile neutropenia (FN) among patients with breast, lung, colon, pancreatic, ovarian cancers or non-Hodgkin's lymphoma (NHL) in the Biologics and Biosimilars Collective Intelligence Consortium's (BBCIC) Distributed Research Network. Methods: We included patients aged > = 20 years who, in 2015-2019, per insurance claims, received any pegfilgrastim or filgrastim products as febrile neutropenia (FN) prophylaxis during the first cycle of chemotherapy posing a high or intermediate FN risk per National Comprehensive Cancer Network guidelines. We compared the FN risk starting at day 5 following day 1 of chemotherapy receipt between products using Poisson regression model with standardized inverse probability weights and robust variance to estimate the Relative Risk (RR) and 95% Confidence intervals (CI). Results: A total of 15, 941 patients received a pegfilgrastim product in cycle 1 of chemotherapy: 15, 115 (95%) pegfilgrastim, 484 (3%) pegfilgrastim_cbqv, 342 (2%) pegfilgrastim_jmdb. 565 patients received a filgrastim product: 284 (50%) filgrastim, 201 (36%) filgrastim_sndz, 80 (14%) tbo-filgrastim. FN events by product were: 346 pegfilgrastim (2.3% of users), 11 pegfilgrastim_cbqv (2.3%), 8 pegfilgrastim_jmdb (2.3%), 13 filgrastim (4.6%), 5 filgrastim_sndz (2.5%), 2 tbo-filgrastim (2.5%). We found no difference in FN incidence when comparing pegfilgrastim_cbqv to pegfilgrastim (RR 0.83, 95% CI 0.41-1.69), pegfilgrastim_jmdb to pegfilgrastim (RR 1.03, 95% CI 0.56-1.92), and pegfilgrastim_jmdb to pegfilgrastim_cbqv (RR 1.11, 95% CI 0.45-2.74). Similarly, we found no difference in FN incidence when comparing filgrastim_sndz to filgrastim (RR 0.46, 95% CI 0.17-1.28), tbo-filgrastim to filgrastim (RR = 0.30, 95% CI 0.06-1.36), or tbo-filgrastim to filgrastim_sndz (RR 0.54, 95% CI 0.10-2.77). Adverse events were rare, with similar rates observed among all products. Conclusions: We observed no significant difference in FN incidence among patients when comparing various G-CSF products, including when biosimilars were compared to their reference counterparts.